2020
DOI: 10.1186/s12871-020-01211-7
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Dexmedetomidine attenuates brain ischemia reperfusion injury possibly via up-regulation of astrocyte Connexin 43

Abstract: Background Astrocyte Connexin 43 (Cx43) is essential for the trophic and protective support of neurons during brain ischemia reperfusion (I/R) injury. It is believed that dexmedetomidine participates in Cx43-mediated effects. However, its mechanisms remained unclear. This study aims to address the relationship and regulation among them. Methods Adult male Sprague-Dawley rats were allocated to the 90-min right middle cerebral arterial occlusion with or without dexmedetomidine pretreatment (5 μg/kg). Neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Microglia-mediated inflammation affects basal lamina integrity and leads to increased permeability of the BBB, ultimately resulting in significant neurovascular disruption [ 35 ]. A previous study showed that the activation of AKT/GSK3β inhibited the proinflammatory “M1” phenotype of microglia and then downregulated IL-6, IL-1β and TNF-α levels [ 36 38 ]. The present study showed that alisol A significantly inhibited the expression of GFAP and Iba1 and reduced the overactivation of glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia-mediated inflammation affects basal lamina integrity and leads to increased permeability of the BBB, ultimately resulting in significant neurovascular disruption [ 35 ]. A previous study showed that the activation of AKT/GSK3β inhibited the proinflammatory “M1” phenotype of microglia and then downregulated IL-6, IL-1β and TNF-α levels [ 36 38 ]. The present study showed that alisol A significantly inhibited the expression of GFAP and Iba1 and reduced the overactivation of glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The significant reduction in the VAS in Group A reveals that DEX could provide analgesia during PELD so as to attenuate inflammatory response and pain-induced oxidative stress. According to the previous study, perioperative DEX administration can effectively reduce the generation of inflammatory mediators in the plasma, which relys on TLR4/MyD88/MAPK/ NF-κB signaling pathway and PI3K-Akt-GSK-3βsignaling pathway [ 24 , 25 ]. In addition, through amelioration of HMGB1-NLRP3 inflammasome-AMPK signaling could DEX play protective action [ 26 ] and DEX has STAT3-dependent anti-inflammatory effects to attenuate the tissue inflammatory cascade response by modulating the JAK2/STAT3 signaling pathway [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Zhai et al (2019) highlighted that Dex attenuates ischemia-induced neuronal apoptosis (Zhai et al, 2019). Dex can protect both cardiomyocytes (Chang et al, 2020) and neurons (Zheng et al, 2020) against ischemia-reperfusion injury through the inhibition of apoptosis. Based on the above findings, we hypothesize that Dex might protect MSCs against ischemia-induced cell death.…”
Section: Introductionmentioning
confidence: 98%